2005
DOI: 10.1038/sj.bdj.4811980
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary dental practice in the UK: indirect restorations and fixed prosthodontics

Abstract: Objectives: To investigate, by questionnaire, the use and selection of materials and techniques for indirect restorations and fixed prosthodontics by dental practitioners in the North West of England and Scotland. Methods: A questionnaire was sent to 1,000 general dental practitioners selected at random from dentists in Scotland and the North West of England. Non-responders were sent another questionnaire after a period of 4 weeks had elapsed. Results: A total of 701 usable questionnaires were returned, giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 19 publications
(19 reference statements)
3
37
1
Order By: Relevance
“…This was considered relevant subsequent to a previous study [3][4][5] and an ever-increasing rate of change in circumstances considered to impact on the clinical practice of dentistry. Information of the type revealed by the present investigation is considered important to understanding, among other factors, trends in oral health provision, attitudes in the profession and future requirements in terms of education and recruitment to studies leading to membership of the dental team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was considered relevant subsequent to a previous study [3][4][5] and an ever-increasing rate of change in circumstances considered to impact on the clinical practice of dentistry. Information of the type revealed by the present investigation is considered important to understanding, among other factors, trends in oral health provision, attitudes in the profession and future requirements in terms of education and recruitment to studies leading to membership of the dental team.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, it was considered timely to investigate the practising arrangements of UK dentists in 2000. [3][4][5] Given the ever-increasing rate of change impacting on the clinical practise of dentistry, it was considered appropriate to repeat the investigation six years later.…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire was circulated previously in 2004 and the results were reported subsequently. [1][2][3] The questionnaire, which comprised of 89 questions, had been piloted by a group of practitioners in the North West and for reasons of comparison no questions were Objectives To investigate, by postal questionnaire, various aspects of primary dental care provision in the United Kingdom. Additionally, to compare the results of this survey with a similar survey completed four years previously.…”
Section: Introductionmentioning
confidence: 99%
“…2 Authors in Sweden and Germany surveying GDPs' treatment concepts for endodontically treated teeth found that practices were not in complete agreement with current recommendations in the literature. 3,4 Although the current practices of GDPs in the UK have been surveyed, 5,6 there is little published work relating these to the uptake of modern restorative principles. 7 Previous efforts have been made to look at how and why dentists decide to replace an existing amalgam restoration with a larger one or with a crown [8][9][10] but advances in bonding technology may have rendered these findings obsolete.…”
mentioning
confidence: 99%
“…12 Developments in adhesive dentistry have provided clinicians with more options, helping them to restore teeth without destructive preparations and repair restorations rather than replacing them, minimising the loss of sound tooth tissue. 5,13,14 introDuCtion Continuing professional development (CPD) courses seek to inform, educate and develop practitioners' patterns of prescribing in line with the evidence base. This may include the introduction of new materials and methods or the modification of existing procedures.…”
mentioning
confidence: 99%